Implementation of knowledge management system in cattle farming - Kusnadi, Edi; Yanitasari, Yessy; Supriyadi, Supriyadi (ILKOM Jurnal Ilmiah, 2021)
Cattle are the livestock of the Bovinae family and subfamily Bovidae. They have been raised for beef and dairy products. Nowadays, beef production does not meet national needs. This is influenced by several factors. One of them is the farming pattern. However, knowledge about cattle farming is still scattered and unstructured. Knowledge Management System (KMS) offers a knowledge system that can be used to create, collect, store, maintain and disseminate knowledge. In this study, KMS for cattle farming has been implemented using the Knowledge Management System Life Cycle (KMSLC) method. The research results are web-based applications regarding cattle farming management that have been tested by experts and users, with the average test results declared good. The features possessed by this KMS application are knowledge capture, knowledge sharing, and knowledge application systems so that they can share knowledge between one user and another. In addition, this application is equipped with a discussion forum that can serve as a place to interact with fellow users or with experts.